Effects of vitamin and mineral supplementation during pregnancy on maternal, birth, child health and development outcomes in low‐ and middle‐income countries: A systematic review. Issue 2 (26th June 2021) - Keats, Emily C.; Oh, Christina; Chau, Tamara; Khalifa, Dina S.; Imdad, Aamer; Bhutta, Zulfiqar A.
Abstract: Background: Almost two billion people who are deficient in vitamins and minerals are women and children in low‐ and middle‐income countries (LMIC). These deficiencies are worsened during pregnancy due to increased energy and nutritional demands, causing adverse outcomes in mother and child. To reduce micronutrient deficiencies, several strategies have been implemented, including diet diversification, large‐scale and targeted fortification, staple crop bio‐fortification and micronutrient supplementation. Objectives: To evaluate and summarize the available evidence on the effects of micronutrient supplementation during pregnancy in LMIC on maternal, fetal, child health and child development outcomes. This review will assess the impact of single micronutrient supplementation (calcium, vitamin A, iron, vitamin D, iodine, zinc, vitamin B12), iron‐folic acid (IFA) supplementation, multiple micronutrient (MMN) supplementation, and lipid‐based nutrient supplementation (LNS) during pregnancy. Search Methods: We searched papers published from 1995 to 31 October 2019 (related programmes and good quality studies pre‐1995 were limited) in CAB Abstracts, CINAHL, Cochrane Central Register of Controlled Trials, Embase, International Initiative for Impact Evaluations, LILACS, Medline, POPLINE, Web of Science, WHOLIS, ProQuest Dissertations & Theses Global, R4D, WHO International Clinical Trials Registry Platform. Non‐indexed grey literature searches were conducted using Google, Google Scholar, and web pages of key international nutrition agencies. Selection Criteria: We included randomized controlled trials (individual and cluster‐randomized) and quasi‐experimental studies that evaluated micronutrient supplementation in healthy, pregnant women of any age and parity living in a LMIC. LMIC were defined by the World Bank Group at the time of the search for this review. While the aim was to include healthy pregnant women, it is likely that these populations had one or more micronutrient deficiencies at baseline; women were not excluded on this basis. Data Collection and Analysis: Two authors independently assessed studies for inclusion and risk of bias, and conducted data extraction. Data were matched to check for accuracy. Quality of evidence was assessed using the GRADE approach. Main Results: A total of 314 papers across 72 studies (451, 723 women) were eligible for inclusion, of which 64 studies (439, 649 women) contributed to meta‐analyses. Seven studies assessed iron‐folic acid (IFA) supplementation versus folic acid; 34 studies assessed MMN vs. IFA; 4 studies assessed LNS vs. MMN; 13 evaluated iron; 13 assessed zinc; 9 evaluated vitamin A; 11 assessed vitamin D; and 6 assessed calcium. Several studies were eligible for inclusion in multiple types of supplementation. IFA compared to folic acid showed a large and significant (48%) reduction in the risk of maternal anaemia (average risk ratio (RR) 0.52, 95% CI 0.41 to 0.66; studies = 5; participants = 15, 540; moderate‐quality evidence). As well, IFA supplementation demonstrated a smaller but significant, 12% reduction in risk of low birthweight (LBW) babies (average RR 0.88, 95% CI 0.78 to 0.99; studies = 4; participants = 17, 257; high‐quality evidence). MMN supplementation was defined as any supplement that contained at least 3 micronutrients. Post‐hoc analyses were conducted, where possible, comparing the differences in effect of MMN with 4+ components and MMN with 3 or 4 components. When compared to iron with or without FA, MMN supplementation reduced the risk of LBW by 15% (average RR 0.85, 95% CI 0.77 to 0.93; studies = 28; participants = 79, 972); this effect was greater in MMN with >4 micronutrients (average RR 0.79, 95% CI 0.71 to 0.88; studies = 19; participants = 68, 138 versus average RR 1.01, 95% CI 0.92 to 1.11; studies = 9; participants = 11, 834). There was a small and significant reduction in the risk of stillbirths (average RR 0.91; 95% CI 0.86 to 0.98; studies = 22; participants = 96, 772) and a small and significant effect on the risk of small‐for‐gestational age (SGA) (average RR 0.93; 95% CI 0.88 to 0.98; studies = 19; participants = 52, 965). For stillbirths and SGA, the effects were greater among those provided MMN with 4+ micronutrients. Children whose mothers had been supplemented with MMN, compared to IFA, demonstrated a 16% reduced risk of diarrhea (average RR 0.84; 95% CI 0.76 to 0.92; studies = 4; participants = 3, 142). LNS supplementation, compared to MMN, made no difference to any outcome; however, the evidence is limited. Iron supplementation, when compared to no iron or placebo, showed a large and significant effect on maternal anaemia, a reduction of 47% (average RR 0.53, 95% CI 0.43 to 0.65; studies = 6; participants = 15, 737; moderate‐quality evidence) and a small and significant effect on LBW (average RR 0.88, 95% CI 0.78 to 0.99; studies = 4; participants = 17, 257; high‐quality evidence). Zinc and vitamin A supplementation, each both compared to placebo, had no impact on any outcome examined with the exception of potentially improving serum/plasma zinc (mean difference (MD) 0.43 umol/L; 95% CI −0.04 to 0.89; studies = 5; participants = 1, 202) and serum/plasma retinol (MD 0.13 umol/L; 95% CI −0.03 to 0.30; studies = 6; participants = 1, 654), respectively. When compared to placebo, vitamin D supplementation may have reduced the risk of preterm births (average RR 0.64; 95% CI 0.40 to 1.04; studies = 7; participants = 1, 262), though the upper CI just crosses the line of no effect. Similarly, calcium supplementation versus placebo may have improved rates of pre‐eclampsia/eclampsia (average RR 0.45; 95% CI 0.19 to 1.06; studies = 4; participants = 9, 616), though the upper CI just crosses 1. Authors' Conclusions: The findings suggest that MMN and vitamin supplementation improve maternal and child health outcomes, including maternal anaemia, LBW, preterm birth, SGA, stillbirths, micronutrient deficiencies, and morbidities, including pre‐eclampsia/eclampsia and diarrhea among children. MMN supplementation demonstrated a beneficial impact on the most number of outcomes. In addition, MMN with >4 micronutrients appeared to be more impactful than MMN with only 3 or 4 micronutrients included in the tablet. Very few studies conducted longitudinal analysis on longer‐term health outcomes for the child, such as anthropometric measures and developmental outcomes; this may be an important area for future research. This review may provide some basis to guide continual discourse around replacing IFA supplementation with MMN along with the use of single micronutrient supplementation programs for specific outcomes.